Quantifying Yield Losses in Canola (Brassica napus) Caused by Verticillium longisporum - Ji Cui; Stephen E. Strelkov; Sheau-Fang Hwang (Horticulturae)
Verticillium stripe, a soilborne disease of canola (Brassica napus) caused by Verticillium longisporum, was first identified on the Canadian Prairies in 2014. Despite its increasing incidence, the impact of this disease on canola yields has not been quantified. To address this gap, the relationship between Verticillium stripe severity and yield was investigated in two canola hybrids, ‘45H31’ and ‘CS2000’, at two infested field sites near St. Albert, Alberta, in 2020 and 2021. In 2020, a year with above-average rainfall, both hybrids developed moderate levels of the disease, whereas in 2021, a drought year, symptoms and signs of infection were milder. Regression analysis indicated that seed yield per plant declined with increasing Verticillium stripe severity in both years of the study. In both hybrids, the relationship between disease severity and yield was best explained by second-degree quadratic equations. Although single-plant seed yield declined by up to 80% with increasing Verticillium stripe severity, these reductions did not translate into significant yield losses at the plot level, suggesting that losses experienced by individual plants were offset by reduced competition among the surviving plants. These results underscore the complexity of assessing disease impacts solely based on symptom severity.